Uncaria tomentosa: adjuvante no tratamento do câncer de mama - Araújo, Maria do Carmo dos Santos (2013)
Cat s Claw (Uncaria tomentosa) is a medicinal plant that has been used in the treatment of different diseases, among them, cancer. Studies show its effects in restoring the cellular DNA, in increasing leukocyte fractions, myelostimulant action, and in producing interleukins, including IL1 and IL6, besides presenting antioxidant, antiproliferative, and assisting in the induction of apoptosis. Breast cancer is the most common malignancy among women. One of the recommended treatments for this pathology is the chemotherapeutic agents whose toxic effects include leucopenia and neutropenia, with high risk of infections. Thus, pharmacological interventions that reduce or prevent adverse effects can have a substantial impact on the treatment of cancer. In this context, the objectives of this study are: to evaluate the effect of Uncaria tomentosa as an adjuvant for breast cancer treatment through a randomized clinical trial and cytotoxic effect, induction of apoptosis in MCF-7 cell lines of breast cancer. Results show that Uncaria tomentosa, used at a dose of 300mg of dried extract (Unha de Gato Herbarium®), per day, is effective in recovery from neutropenia induced by chemotherapy in women diagnosed with invasive ductal Carcinoma Stage II, and it is also capable of restoring the cellular DNA. Extracts of Uncaria tomentosa exerted a cytotoxic activity in MCF-7 cells associated with cell death by apoptosis through the activation of caspases 3/8, and did not trigger changes in the response profile of cells undergoing apoptosis, remaining similar to doxorubicin. Thus, Uncaria tomentosa may be a beneficial option as an adjuvant therapy for breast cancer.